Aurignacian lithic economy : ecological perspectives from Southwestern France - Blades, Brooke S. (Interdisciplinary contributions to archaeology., 2001)
Drawing data from a classic region for Paleolithic research in Europe, this book explores how early modern humans obtained lithic raw materials and analyzes the different utilization patterns for locally available materials compared with those from a greater distance. The author locates these patterns within an ecological context and argues that early modern humans selected specific mobility strategies to accommodate changes in subsistence environments.